2005
DOI: 10.1051/0004-6361:20040249
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of the chromospheric activity in Solar-type stars – The Hα line

Abstract: Abstract.A calibration of Hα as both a chromospheric diagnostic and an age indicator is presented, complementing the works previously done on this subject (Herbig 1985;Pasquini & Pallavicini 1991). The chromospheric diagnostic was built with a statistically significant sample, covering nine years of observations, and including 175 solar neighborhood stars. Regarding the age indicator, the presence of stars for which very accurate ages are determined, such as those belonging to clusters and kinematic groups, le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 23 publications
8
78
0
Order By: Relevance
“…The table lists the flux in the centre of the Hα line (F Hα ), computed by Lyra & Porto de Mello (2005) and used as a chromospheric activity indicator (the larger the value of F Hα , the higher the level of chromospheric activity). The uncertainty for this parameter is 0.5 × 10 5 erg cm −2 s −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The table lists the flux in the centre of the Hα line (F Hα ), computed by Lyra & Porto de Mello (2005) and used as a chromospheric activity indicator (the larger the value of F Hα , the higher the level of chromospheric activity). The uncertainty for this parameter is 0.5 × 10 5 erg cm −2 s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Lyra & Porto de Mello (2005) applied this method to solar neighbourhood stars, and values of T Hα eff for our sample were used as a third T eff indicator, with an uncertainty σ(T Hα eff ) = 50 K.…”
Section: Photometric and Hα Effective Temperaturesmentioning
confidence: 99%
“…However, it is possible to address the chromospheric infilling of the Hα core. Lyra & Porto de Mello (2005) argue that there are even some advantages compared to Ca II H&K. Fuhrmann (2004) note that the Hα cores of Ursa Major stars are filled-in by about 10% compared to inactive main-sequence stars of similar effective temperature. The present work allows one to verify this behaviour for a larger sample of UMa group members.…”
Section: Infilling Of the Hα Corementioning
confidence: 99%
“…To more reliably compare the chromospheric infilling of UMa group members with that of other stellar groups, in particular the Pleiades and the Hyades, the chromospheric flux is measured according to the method of Lyra & Porto de Mello (2005). They showed that members of different stellar groups display a different average level of chromospheric flux.…”
Section: Infilling Of the Hα Corementioning
confidence: 99%
See 1 more Smart Citation